Flexural performance of TRC-strengthened RC beam under chloride environment. Issue 5 (13th September 2018) - Shi-ping, Yin; Yulin, Yu; Xi, Yunping
Abstract : Purpose: Textile reinforced concrete (TRC) has excellent bearing capacity and anti-crack and corrosion resistance capacity, which are suitable for strengthening concrete structure under harsh environments. Design/methodology/approach: In this thesis, flexural properties of RC beams strengthened with TRC under chloride wet–dry cycles were studied and the effects of the concentration of the salt solution, number of wet–dry cycles, bending stress level and TRC form were considered. Four-point bend loading mode was adopted for the step-loading procedure. Findings: As the number of wet–dry cycles was relatively few, the trend of the yield and ultimate load with the increasing concentration of salt solution and wet–dry cycles were not obvious. However, the beams under high sustained bending stress level (0.5) had a decrease in the bearing capacity and an increase in mid-span deflection because of the larger degree of the corrosion of steel bars and the weaker bond capacity between the steel bar and concrete. Besides, there was little difference between the precast TRC plate and the casting TRC on beams in terms of the capacity of anti-crack, bearing and deflection. Research limitations/implications: In this paper, preliminary work has been carried out, but some of the factors were not comprehensive considered, which are inevitable. As the time of dry–wet cycles was short and TRC layer had good anti-crack and anti-permeability performance, smaller chloride ions' penetration resulted in the corrosion ratio of steel bars to be lower. Practical implications: It should be noted that under high corrosion rates of the reinforcement, the whole TRC strengthening layer might be spalled off if only the strengthening form at the beam bottom is used, and thus the U-type strengthening form could be considered, which means that the beam is strengthened at both the bottom and side surfaces. Originality/value: This research only considers the flexural performance of the beams strengthened with TRC in conventional environment, and there is little research on the TRC-strengthened beam under corrosion environment. On the basis of previous research, this paper carried out the experimental study on beams strengthened with TRC under chloride wet–dry cycle environment, and the effects of the concentration of the salt solution, number of wet–dry cycles, bending stress level and TRC form were considered.